HYDROPERICARDIUM IN BROILER CHICKENS IN IRAQ: ISOLATION AND IDENTIFICATION OF THE CAUSATIVE VIRUS - M.Odisho, Shoney; Al-Bana, Anions; KH.Majeed , Amjad (The Iraqi Journal of Veterinary Medicine, 1996)
An adenovirus was successfully isolated from infected liver, spleen and pericardial fluid from infected broiler chicks in primary cell cultures prepared from chicken embryo liver and kidneys. The isolated virus induced cytopathogenic effect (CPE) in infected cell cultures which consisted of cell granulation, aggregation and rounding of infectedd cells. An adenovirus like morphology was identified by Electron microscope examination. In addition the isolated virus was diagnosed, by agar gel diffusion test (AGD). Indirect immune fluorescenct test (IFA) and serum neutralization (SN). Using reference hyperimmune serum and sera from recovered chicks